2016
DOI: 10.1080/13102818.2016.1262750
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of Moringa peregrina Forssk as an antimicrobial agent against multi-drug-resistant Salmonella sp.

Abstract: The emergence of multi-drug-resistant (MDR) pathogenic bacteria is considered as a global problem. The aim of this study was to evaluate the antimicrobial inhibitory effects of the oily aqueous extract of Moringa peregrina Forssk against MDR clinical Salmonella enterica isolates. Four MDR S. enterica isolates were proved to have a gene mutation in amino acids codon 83 and 87 of gyrA and 67, 76 and 80 of parC gene by polymerase chain reaction (PCR) amplification and sequencing. The active components of M. pregr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…In Figure 6, it is obvious that, after being treated with BITC, the adhesion of the biofilm was significantly reduced, and S. typhimurium was wrinkled and deformed at 1/4 MIC concentration. This conclusion is consistent with the results of Borges et al, and Saleh et al, showing that BITC significantly inhibits S. typhimurium growth and changes the integrity of biofilms [15,17]. These results indicate that BITC has significant influence on the biofilm formation characteristics of S. typhimurium.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Figure 6, it is obvious that, after being treated with BITC, the adhesion of the biofilm was significantly reduced, and S. typhimurium was wrinkled and deformed at 1/4 MIC concentration. This conclusion is consistent with the results of Borges et al, and Saleh et al, showing that BITC significantly inhibits S. typhimurium growth and changes the integrity of biofilms [15,17]. These results indicate that BITC has significant influence on the biofilm formation characteristics of S. typhimurium.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, BITC antibacterial mechanisms in foodborne bacteria have been widely studied. For example, the biofilm integrity, bacterial morphology, membrane potential, ATP, and membrane hydrophilicity of bacteria treated with BITC have been investigated [15][16][17]. However, the mechanism of antibacterial activity of BITC on S. typhimurium is still unclear, and further studies are needs.…”
Section: Introductionmentioning
confidence: 99%
“…M. oleifera is regarded as a multipurpose tree and shrub species and it is used as a food, fodder, medicine, fencing, gum, and firewood, as well as a coagulant to treat polluted water [27]. M. peregrina is also considered a medicinally important plant due to its antioxidant, antifungal, and antibacterial properties [28].…”
mentioning
confidence: 99%
“…At a concentration of 40 mg/100 μl, the ethanol extract of in vitro plantlets of M. peregrina showed the highest zone of inhibition against S. aureus (Alrayes et al, 2016 ). Aqueous extract of M. peregrina seeds was investigated for antibacterial activity against clinically isolated multidrug resistant Salmonella species (Saleh et al, 2017 ). The results showed that the extracts exhibited good antibacterial activity against the multidrug resistant Salmonella isolates.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Recently, M. peregrina is gaining more attention due to traditional, nutritional, industrial and medicinal values. As this plant has wide range of medicinal uses, it has been screened for various pharmacological activities in the past few decades (Marwah et al, 2007 ; Soltan and Zaki, 2009 ; Koheil et al, 2011 ; Dehshahri et al, 2012 ; Lalas et al, 2012 ; Al-Owaisi et al, 2014 ; Moustafa et al, 2014 ; Majali et al, 2015 ; Safaeian et al, 2015 ; Ullah et al, 2015 ; Alrayes et al, 2016 ; El-Awady et al, 2016 ; Azim et al, 2017 ; Elabd et al, 2017 ; Saleh et al, 2017 ). Few active molecules were also isolated, identified and reported for various pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%